A selanylimidazopyridine (3-SePh-IP) reverses the prodepressant- and anxiogenic-like effects of a high-fat/high-fructose diet in mice. (2nd March 2021) - Veloso, Izolene Corrêa; Delanogare, Eslen; Machado, Adriano Emanuel; Braga, Sara Pereira; Rosa, Giovana Karoline; De Bem, Andreza Fabro; Rafique, Jamal; Saba, Sumbal; da Trindade, Roberth Nascimento; Galetto, Fábio Zazyki; Moreira, Eduardo Luiz Gasnhar
Abstract: Objective: While chronic feeding with high-fat or high-sugar diets is known related to obesity and type 2 diabetes, later data have indicated that it is also related to depression and anxiety appearance. In this regard, multi-target drugs raise considerable interest as promising therapeutic solutions to complex diseases. Considering the pharmacological effects of the imidazopyridine-derivative moiety imidazo[1, 2- a ]pyridine and the organoselenium molecules, the combination of both could be a feasible strategy to develop efficient drugs to handle obesity and related comorbidities, for example dyslipidemia and mood disorders. Methods: The antidepressant- and anxiolytic-like properties of a selanylimidazopyridine compound, 2-Phenyl-3-(phenylselanyl)imidazo[1, 2- a ]pyridine (3-SePh-IP), were evaluated on high-fat/high-fructose diet (HFFD)-fed female Swiss mice. Key findings: Our results showed that a short-term HFFD (16 days) could promote a significant body weight gain, hypercholesterolemia, glucose intolerance, and anxiety- and depressive-like behaviour in mice. Concomitant treatment with 3-SePh-IP (10 mg/kg; i.p.) attenuated the HFFD-induced increase in cholesterol levels and blunted the anxiety- and depressive-like behaviour in mice. Conclusions: 3-SePh-IP holds multimodal pharmacological properties, which provide a rationale for further studies, for example to assess the underlying mechanisms linked to its anxiolytic- and antidepressive-like activities. Graphical Abstract: